2007
DOI: 10.1111/j.1467-9310.2007.00486.x
|View full text |Cite
|
Sign up to set email alerts
|

Your new product development (NPD) is only as good as your process: an exploratory analysis of new NPD process design and implementation

Abstract: Given industry competitiveness, how do firms' new product development (NPD) process designs differ when responding to an innovation mandate? How do NPD design elements differ across firms when implementing NPD processes? These design elements are strategic business unit (SBU) senior management involvement, business case content, customer interactions, and cross-functional integration. What are the consequences of different combinations of NPD process design elements for innovation productivity? We explore thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 86 publications
2
65
0
5
Order By: Relevance
“…The work by Harmancioglu et al [2] is perhaps the closest reference to our own study. They conducted a collective case study at three strategic business units that operate in the building materials industry, i.e.…”
Section: Related Workmentioning
confidence: 91%
See 1 more Smart Citation
“…The work by Harmancioglu et al [2] is perhaps the closest reference to our own study. They conducted a collective case study at three strategic business units that operate in the building materials industry, i.e.…”
Section: Related Workmentioning
confidence: 91%
“…But it has been widely described as a complex process. In the words of Harmancioglu et al [2], there is no 'one-size-fits-all' solution. In their realistic and myth-breaking work, McIvor et al [4] argue that communication problems were identified during "early supplier involvement" (ESI) in a series of case studies involving a number of multinational corporations.…”
Section: Related Workmentioning
confidence: 99%
“…The communication aspect of the negotiation process requires parties exchange information to make offers and influence and motivate opposing parties to make counter offers. In spite of the importance of negotiation, achieving higher quality, lower cost and shorter cycle time has been the primary goal of collaborative product development (Noori and Lee 2004, Li et al 2005, Molina et al 2005, Ouzizi et al 2006, Harmancioglu et al 2007, Pol et al 2007, Hu et al 2010. The literature on collaborative product development generally does not effectively support group decisionmaking and negotiation among potential manufacturing partners (Jing and Lu 2010).…”
Section: Introductionmentioning
confidence: 99%
“…O desenvolvimento de produtos é uma das capacidades dinâmicas mais importantes de uma empresa (HARMANCIOGLU et al, 2007), sendo um contribuidor significativo do crescimento da organização (FLINT, 2002;FRISHAMMAR;YLINENPÄÄ, 2007;JUDSON et al, 2006;JUDSON et al, 2009;ZAHAY;GRIFFIN;FREDERICKS, 2004 (HARMANCIOGLU et al, 2007).…”
Section: Processo De Desenvolvimento De Produtos (Pdp)unclassified
“…O processo de desenvolvimento de produtos, doravante denominado PDP, é uma das ações consagradas para a perpetuação de uma empresa no mercado em que atua (FLINT, 2002;FRISHAMMAR;YLINENPÄÄ, 2007;HARMANCIOGLU et al, 2007;JUDSON et al, 2006;JUDSON et al, 2009;ZAHAY;GRIFFIN;FREDERICKS, 2004).…”
Section: Introductionunclassified